A time of change : questioning the "collapse" of Anuradhapura, Sri Lanka - Strickland, Keir Magalie (Archaeopress archaeology., 2017)
This work reassesses the apparent collapse of Anuradhapura, Sri Lanka, through explicit reference to the archaeological record. The study of Anuradhapura's terminal period has long been dominated by an over-reliance upon textual sources, resulting in the establishment of a monocausal and politically charged narrative that depicts a violent eleventh century invasion by the South Indian Chola Empire as the primary cause of Anuradhapura's collapse, bringing to an end over a millennium of rule from Sri Lanka's first capital. Such is the dominance of this narrative that few alternative explanations for the abandonment of Anuradhapura have ever been posited, with just two alternative models ever described; epidemic malaria, and an imperial economic model.